If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (ax + c)(bx + d) = (bx + c)(ax + d) Multiply (ax + c) * (bx + d) (ax(bx + d) + c(bx + d)) = (bx + c)(ax + d) ((bx * ax + d * ax) + c(bx + d)) = (bx + c)(ax + d) ((abx2 + adx) + c(bx + d)) = (bx + c)(ax + d) (abx2 + adx + (bx * c + d * c)) = (bx + c)(ax + d) (abx2 + adx + (bcx + cd)) = (bx + c)(ax + d) (abx2 + adx + bcx + cd) = (bx + c)(ax + d) Multiply (bx + c) * (ax + d) abx2 + adx + bcx + cd = (bx(ax + d) + c(ax + d)) abx2 + adx + bcx + cd = ((ax * bx + d * bx) + c(ax + d)) abx2 + adx + bcx + cd = ((abx2 + bdx) + c(ax + d)) abx2 + adx + bcx + cd = (abx2 + bdx + (ax * c + d * c)) abx2 + adx + bcx + cd = (abx2 + bdx + (acx + cd)) Reorder the terms: abx2 + adx + bcx + cd = (abx2 + acx + bdx + cd) abx2 + adx + bcx + cd = (abx2 + acx + bdx + cd) Add '-1abx2' to each side of the equation. abx2 + adx + bcx + -1abx2 + cd = abx2 + acx + bdx + -1abx2 + cd Reorder the terms: abx2 + -1abx2 + adx + bcx + cd = abx2 + acx + bdx + -1abx2 + cd Combine like terms: abx2 + -1abx2 = 0 0 + adx + bcx + cd = abx2 + acx + bdx + -1abx2 + cd adx + bcx + cd = abx2 + acx + bdx + -1abx2 + cd Reorder the terms: adx + bcx + cd = abx2 + -1abx2 + acx + bdx + cd Combine like terms: abx2 + -1abx2 = 0 adx + bcx + cd = 0 + acx + bdx + cd adx + bcx + cd = acx + bdx + cd Add '-1cd' to each side of the equation. adx + bcx + cd + -1cd = acx + bdx + cd + -1cd Combine like terms: cd + -1cd = 0 adx + bcx + 0 = acx + bdx + cd + -1cd adx + bcx = acx + bdx + cd + -1cd Combine like terms: cd + -1cd = 0 adx + bcx = acx + bdx + 0 adx + bcx = acx + bdx Solving adx + bcx = acx + bdx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1acx' to each side of the equation. adx + -1acx + bcx = acx + -1acx + bdx Reorder the terms: -1acx + adx + bcx = acx + -1acx + bdx Combine like terms: acx + -1acx = 0 -1acx + adx + bcx = 0 + bdx -1acx + adx + bcx = bdx Add '-1bcx' to each side of the equation. -1acx + adx + bcx + -1bcx = -1bcx + bdx Combine like terms: bcx + -1bcx = 0 -1acx + adx + 0 = -1bcx + bdx -1acx + adx = -1bcx + bdx Reorder the terms: -1acx + adx + bcx + -1bdx = -1bcx + bcx + bdx + -1bdx Combine like terms: -1bcx + bcx = 0 -1acx + adx + bcx + -1bdx = 0 + bdx + -1bdx -1acx + adx + bcx + -1bdx = bdx + -1bdx Combine like terms: bdx + -1bdx = 0 -1acx + adx + bcx + -1bdx = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-1ac + ad + bc + -1bd) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing a to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x = 0 + -1x Remove the zero: 0 = -1x Simplifying 0 = -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1ac + ad + bc + -1bd)' equal to zero and attempt to solve: Simplifying -1ac + ad + bc + -1bd = 0 Solving -1ac + ad + bc + -1bd = 0 Move all terms containing a to the left, all other terms to the right. Add '-1bc' to each side of the equation. -1ac + ad + bc + -1bc + -1bd = 0 + -1bc Combine like terms: bc + -1bc = 0 -1ac + ad + 0 + -1bd = 0 + -1bc -1ac + ad + -1bd = 0 + -1bc Remove the zero: -1ac + ad + -1bd = -1bc Add 'bd' to each side of the equation. -1ac + ad + -1bd + bd = -1bc + bd Combine like terms: -1bd + bd = 0 -1ac + ad + 0 = -1bc + bd -1ac + ad = -1bc + bd The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 10d-8=3d-17-2d | | 7x+16-3x=12-6x-6 | | 6x+y=8 | | S=3(r^3)t | | p-5=-12+p | | S=3r^3t | | 2a-5+12c=2a+b | | 5z-12=5z+15 | | (13x-25)+(9x+3)=77 | | -100x=10x^2 | | (0.1x+1)*.1x=2x | | -5(t-1)+9t=7t-6 | | 83=x+59 | | 63-n=15 | | 7+5b=37 | | 42-5=x | | 6+3+c=19 | | (5x-6)+(2x+5)=180 | | 17-x=16-5 | | 37-12=c-5 | | 6+2+n=19 | | 56=x-7 | | -.3y+.1=.5 | | 50-t^2=0 | | 3x+6y=39 | | 9z-z=-1+6z-3-2 | | h=-16t^2+144 | | 5-2x=3x-1 | | 11y+2=10y-4 | | 2x-7=-7+5x | | -3+2x=-6x-91 | | 3x+7=6x-20 |